2008
DOI: 10.1136/bjo.2008.144055
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence imaging of pingueculae

Abstract: Pingueculae display hyperautofluorescence in AF imaging. The real size of pingueculae may be estimated by its AF characteristics, which is mostly larger than the visible lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The presence of fluorescence (in at least one region) was 0% in 27 children aged 3 to 8 years, 6 of 23 (26%) for those ages 9-11 years and 17 of 21 (81%) for those ages 12 to 15 years. Using a confocal scanning laser ophthalmoscope, Utine et al 30 measured AF in 40 eyes in 23 patients with pinguceulae. In all of the cases, the size of AF in the pinguecula was greater than the extent of the visible pinguecula on slit-lamp examination in 71.4% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of fluorescence (in at least one region) was 0% in 27 children aged 3 to 8 years, 6 of 23 (26%) for those ages 9-11 years and 17 of 21 (81%) for those ages 12 to 15 years. Using a confocal scanning laser ophthalmoscope, Utine et al 30 measured AF in 40 eyes in 23 patients with pinguceulae. In all of the cases, the size of AF in the pinguecula was greater than the extent of the visible pinguecula on slit-lamp examination in 71.4% of the lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they found that a Vogt limbal girdle displayed hyperautofluorescence, but arcus senillis did not. 30 AF of the fundus has been used in the imaging of several posterior segment diseases to detect changes in lipofuscin in the retinal pigment epithelium. Such disorders have included rare diseases such as central areolar choroidal dystrophy, 31 Stargardt dystrophy and fundus flavimaculatus, 32 Kjellin's syndrome, 33 multifocal choroiditis and panuveitis, 34 Best's vitelliform dystrophy 35 and birdshot chorioretinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study, to our knowledge, to measure CUVAF area using blue laser autofluorescence on a cSLO. Utine and colleagues described a similar method of detecting autofluorescence within pingueculae using the same cSLO; however, they did not quantify CUVAF area in their study . The ability to use a commercially available cSLO, that is already present in many ophthalmic clinics to detect and measure CUVAF area, allows CUVAF imaging to be more easily adopted by clinicians and researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Utine et al [9] demonstrated that hyper-AF originates from pingueculae using confocal scanning laser ophthalmoscopy. They compared the anterior images to hyper-fluorescence areas.…”
Section: Discussionmentioning
confidence: 99%
“…Utine et al [9] reported that pingueculae display hyper-AF on confocal scanning laser ophthalmoscopy. The actual pinguecula size can be estimated by AF characteristics, and is generally larger than the visible lesion size.…”
mentioning
confidence: 99%